Type Ia supernovae rates and galaxy clustering from the CFHT supernova legacy survey - Graham, M; Pritchet, C; Sullivan, M; Gwyn, S; Neill, J; Hsiao, E; Astier, P; Balam, D; Balland, C; Basa, S; Carlberg, R; Conley, A; et al. (2008)
The Canada-France-Hawaii Telescope Supernova Legacy Survey (CFHT SNLS) has created a large homogeneous database of intermediate redshift (0.2 < z < 1.0) type Ia supernovae (SNe Ia). The SNLS team has shown that correlations exist between SN Ia rates, properties, and host galaxy star-formation rates (SFRs). The SNLS SN Ia database has now been combined with a photometric redshift galaxy catalog and an optical galaxy cluster catalog to investigate the possible influence of galaxy clustering on the SN Ia rate, over and above the expected effect due to the dependence of SFR on clustering through the morphology-density relation. We identify three cluster SNe Ia, plus three additional possible cluster SNe Ia, and find the SN Ia rate per unit mass in clusters at intermediate redshifts is consistent with the rate per unit mass in field early-type galaxies and the SN Ia cluster rate from low-redshift cluster targeted surveys. We also find the number of SNe Ia in cluster environments to be within a factor of 2 of expectations from the two-component SN Ia rate model. © 2008. The American Astronomical Society. All rights reserved.